Lee King and the change in libraries and librarians´ roles: open reflections for discussion - Tosete, Francisco (Anuario ThinkEPI, 2009)
Digital information, digital books and the World Wide Web are gaining an increasing and accelerated importance over paper resources. Therefore, it is time for librarians to begin to assume new roles, including the construction, maintenance and management of websites for each library, as long as its resources permit. Acquisition and application of information architecture and usability skills are essential for good design of these digital libraries, along with the identification of valuable resources on the Web, the development of repositories and the creation and management of digital communities around the library´s website using the tools of Web 2.0. This process should be accompanied by corresponding changes at the political level to facilitate the allocation of the financial resources, technology, training and human resources necessary to do so.